Analisis Penggunaan Tiktok Terhadap Perubahan Perilaku Komunikasi Generasi Z - Maretha, Angel; Nur, Annisa Khairin Pebrianti; Saputra, Rio Dwi Harry; Anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to analyze how TikTok social media users communicate, especially in nonverbal communication among Generation Z. This study uses a qualitative approach, collecting data through interviews and observations of friends who are active on TikTok. The data collection method is digital ethnography, which involves participant observation of Generation Z's communication activities, as well as observing and collecting data on how users interact and communicate on TikTok. This study reveals that Generation Z tends to use nonverbal communication on the TikTok platform. They often enjoy videos that match their interests and the latest trends, and create content inspired by what they watch. Although the variety of content they watch is broad, several major trends emerge, including lectures, sports, news, car rentals, policing, preaching, nature, and cooking. Most of the participants in this study were male, but TikTok users still claim to be entertained and inspired by the content they consume.